Recent advances in the development of RIPK2 modulators for the treatment of inflammatory diseases - Pham, Anh-Tuan; Ghilardi, Amanda Franceschini; Sun, Lijun (Frontiers in Pharmacology, 2023)
Receptor-interacting serine/threonine kinase 2 (RIPK2) is a vital immunomodulator that plays critical roles in nucleotide-binding oligomerization domain 1 (NOD1), NOD2, and Toll-like receptors (TLRs) signaling. Stimulated NOD1, NOD2, and TLRs interact with RIPK2 and lead to the activation of nuclear factor kappa B (NF-κB) and mitogen-activated protein kinases (MAPK), followed by the production of pro-inflammatory cytokines such as TNF-α, IL-6, and IL-12/23. Defects in NOD/RIPK2 signaling are associated with numerous inflammatory diseases, including asthma, sarcoidosis, inflammatory bowel disease (Crohn’s disease and ulcerative colitis), multiple sclerosis, and Blau syndrome. As RIPK2 is a crucial element of innate immunity, small molecules regulating RIPK2 functions are attractive to establish novel immunotherapies. The increased interest in developing RIPK2 inhibitors has led to the clinical investigations of novel drug candidates. In this review, we attempt to summarize recent advances in the development of RIPK2 inhibitors and degraders.